The living building challenge roots and rise of the world's greenest standard - Thomas, Mary Adam (Ecotone Publishing, 2016)
"The living building challenge: roots and rise of the world's greenest standard delves into the profoundly rigorous certification program recognized by the green design-build movement as the most inspirational and sustainable standard in the world. Author Mary Adam Thomas explores the history and ideas that influenced visionary designer Jason F. McLennan to develop the Challenge, reports on its dramatic launch, illuminates Living Building pioneers and projects, and summarizes the global attention the Standard generated in its first ten years. Dozens of industry notables add their voices to this history, rounding out a rich and engaging overview of the past, present, and highly anticipated future of the Living Building Challenge"